SINERGISTIC COMBINATION OF ALOE VERA AND KERSEN LEAF EXTRACTS FOR INHIBITION OF THE GROWTH OF Staphylococcus aureus 25923 - Nanik Sulistyani; Zikri Almahdi; Zainab -; Alfian Syarifuddin (Universitas Muhammadiyah Magelang, 2022)
Aloe vera leaf (Aloe vera L.) and cherry leaf (Muntingia calabura L.) contain bioactive compounds that serve as the potential antibacterial agent. The combination treatment of multiple extracts can produce a stronger effect than a single compound. This study aims to determine the synergistic combination of aloe vera leaf extract (EDLB) and cherry leaf extract (EDK) as an antibacterial agent against Staphylococcus aureus ATCC 25923. The extract was obtained by maceration using 96% ethanol. Chemical content in the extract was analyzed by tube test and thin layer chromatography (TLC). Antibacterial activity against S. aureus ATCC 25923 was measured by the checkerboard microdilution method on a 96 well microplate. The effect of the combination of extracts on antibacterial activity was based on the fractional inhibitory concentration index (FICI) value. EDLB and EDK contain flavonoids, tannins, alkaloids, and saponins. The second combination showed a synergistic effect with a FICI value of 0.5 in inhibiting the growth of S. aureus with minimal inhibitory levels in a mixture of 0.625 mg/mL EDLB and 2.5 mg/mL EDK.